Kemampuan Roll Depan Ditinjau Dari Kelenturan Otot Perut Mahasiswa Kepelatihan Olahraga Universitas Pejuang Republik Indonesia - Rerung, Charmila Tandi (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the relationship between abdominal flexibility and forward roll ability among sports coaching students at Universitas Pejuang Republik Indonesia. Floor xercises, particularly the forward roll movement, require a combination of strength, flexibility, and coordination. The research employs a quantitative approach with a correlational design, involving 21 students as the sample. Abdominal flexibility data is measured using the sit and reach test, while forward roll ability is assessed using a validated scoring rubric. The analysis results indicate a Pearson correlation coefficient of 0.755 with a significance value of 0.012, demonstrating a significant positive relationship between abdominal flexibility and forward roll ability. These findings suggest that improving abdominal flexibility contributes to enhanced forward roll performance. The study recommends increasing abdominal flexibility training to support better mastery of forward roll techniques in floor exercises.